The cAMP-PKA Signaling Pathway Regulates Pathogenicity, Hyphal Growth, Appressorial Formation, Conidiation, and Stress Tolerance in Colletotrichum higginsianum - Zhu, Wenjun; Zhou, Man; Xiong, Zeyang; Peng, Fang; Wei, Wei (Frontiers in Microbiology, 2017)
Colletotrichum higginsianum is an economically important pathogen that causes anthracnose disease in a wide range of cruciferous crops. Understanding the mechanisms of the cruciferous plant–C. higginsianum interactions will be important in facilitating efficient control of anthracnose diseases. The cAMP-PKA signaling pathway plays important roles in diverse physiological processes of multiple pathogens. C. higginsianum contains two genes, ChPKA1 and ChPKA2, that encode the catalytic subunits of cyclic AMP (cAMP)-dependent protein kinase A (PKA). To analyze the role of cAMP signaling pathway in pathogenicity and development in C. higginsianum, we characterized ChPKA1 and ChPKA2 genes, and adenylate cyclase (ChAC) gene. The ChPKA1 and ChAC deletion mutants were unable to cause disease and significantly reduced in hyphal growth, tolerance to cell wall inhibitors, conidiation and appressorial formation with abnormal germ tubes, but they had an increased tolerance to elevated temperatures and exogenous H2O2. In contrast, the ChPKA2 mutant had no detectable alteration of phenotypes, suggesting that ChPKA1 contributes mainly to PKA activities in C. higginsianum. Moreover, we failed to generate ΔChPKA1ChPKA2 double mutant, indicating that deletion of both PKA catalytic subunits is lethal in C. higginsianum and the two catalytic subunits possibly have overlapping functions. These results indicated that ChPKA1 is the major PKA catalytic subunit in cAMP-PKA signaling pathway and plays significant roles in hyphal growth, pathogenicity, appressorial formation, conidiation and stress tolerance in C. higginsianum.